C/EBPβ enhances platinum resistance of ovarian cancer cells by reprogramming H3K79 methylation - Dan Liu (Nature Portfolio, 2018)
In ovarian cancer, the mechanism of chemoresistance is a key question. Here, the authors demonstrate that C/EBPβ and DOT1L together increase methylation of H3K79, which upregulates expression of oncogenic genes and drives poor platinum response and poor survival in ovarian cancer.